Rethinking 'Res Judicata Pro Varitate Habetur' in Indonesian Judiciary: Memikirkan Kembali 'Res Judicata Pro Varitate Habetur' dalam Peradilan Indonesia - Fathor, Fathorrahman; Widiarto, Aan Eko (Indonesian Journal of Law and Economics Review, 2024)
This research explores the principle of "Res Judicata Pro Varitate Habetur," a legal doctrine asserting that a judicial decision with legal authority must be considered correct and binding. Focusing on its application in the decisions of the Constitutional Court (MK) and the Supreme Court (MA) of Indonesia, the study emphasizes the authority and differences in the finality of their rulings. It proposes a conceptual update to "Res Judicata Pro Varitate Habetur" aimed at enhancing public access to legal truth, considering the need to balance legal certainty with judicial system improvements. The research employs a Juridical-Normative method, incorporating conceptual, juridical, and case study approaches. The conceptual approach underscores the importance of understanding legal concepts as a preliminary step in analyzing legal norms. This approach involves the analysis of legal texts, the objectives of the law, and the relevant legal system. The juridical approach involves understanding and analyzing law by referring to the applicable written norms, while the case study approach involves analyzing court decisions or relevant legal cases. The findings highlight the role of this principle in maintaining legal certainty, and suggest that its conceptual update could enhance public access to legal truth and contribute to legal thought on future judicial system reform. Highlights: Conceptual Reevaluation: The study emphasizes rethinking the 'Res Judicata Pro Varitate Habetur' principle to better balance legal certainty and judicial fairness in Indonesia. Methodological Approach: Employing a Juridical-Normative method, the research integrates conceptual analysis, legal norms study, and case examination for comprehensive insights. Implications for Judicial Reform: Findings suggest potential improvements in public access to justice and contribute to broader discussions on reforming the Indonesian judicial system. Keywords: Res Judicata Pro Varitate Habetur, Indonesian Judiciary, Legal Certainty, Judicial Reform, Public Access to Justice